Learning Management and School Discipline in Improving Student Achievement - Nisak, Hernik Khoirun (STAI MA'ARIF MAGETAN, INDONESIA, 2021)
Learning management has a very important role for the world of education because from there, the process of managing educational institutions with educational components and all related matters to achieve the goals that have been set effectively and efficiently, of course all cannot be separated from the role of discipline, the notion of discipline. according to Tulus Tu'us is orderly obedience or controlling behavior, self-control, self-control, so here with discipline through the learning process can improve student achievement through several factors such as intelligence, talent, interest and attention, motive factors, learning methods, family environment and school.